Improving psychological well-being among undergraduates: how creativity in learning can contribute? - Ahmad Zamri Khairani; Hasni Shamsuddin; Izazol Idris (Penerbit Universiti Kebangsaan Malaysia, 2019)
Psychological well-being (PWB) is considered an important variable since it correlates with many other important variables, particularly in mental health. Nevertheless, studies on PWB among university un-dergraduates are limited. This in turn, limits our ability to provide interventions to increase their PWB. As such, the purpose of this study is to assess levels of psychological well-being among undergraduates and to suggest how creativity can contribute to the enhancement of PWB. We also assessed PWB of the undergraduates with regards to gender and years of study. A total of 1965 undergraduates from seven local public universities participated in this cross-sectional survey study. Responses from the Flourishing Scale was used to assess the levels of PWB as well as comparing the mean score of the undergraduates’ PWB in terms of gender and years of study. Results showed that 256 undergraduates fall under the low and moderate low levels, with the majority of them are from the first year cohort. The undergraduates demonstrated the highest mean score with regards to leading purposeful and meaningful life at university but scored low in terms of engagement in their daily activities. We also reported that gender and age have significant effects on the PWB of the undergraduates. We discussed three methods, namely, open-ended projects, brainstorming sessions, and visualisation that can be incorporated into teaching and learning that can enhance creativity. Based on a review of past studies, we argue that incorporating creativity can contribute to enhancing undergraduates' PWB.